2006
DOI: 10.1002/ejic.200600554
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Uranium(VI) with Thiodiacetic Acid in Solution at 10–85 °C

Abstract: The protonation of thiodiacetate and its complexation with uranium(VI) in 1.05 mol kg -1 NaClO 4 are studied at variable temperatures (10-85°C). Three U VI complexes (UO 2 L, UO 2 HL + , and UO 2 HL 2 -, where L is thiodiacetate) are identified in this temperature range. The formation constants and the enthalpies of complexation are determined by potentiometry and calorimetry. The complexation of uranium(VI) with thiodiacetate becomes more endothermic at higher temperatures. However, the complexes become stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…The increase of entropy with the temperature could be the consequence of a more disordered bulk water structure at higher temperatures due to the perturbation by thermal movements. In the process of complexation, the solvating water molecules are released to an already expanded and more disordered bulk solvent [27]. As a result, the net gain in the complexation entropy is larger at higher temperatures.…”
Section: Enthalpy Of Complexation Between U(vi) and Sulfate At Elevatmentioning
confidence: 99%
“…The increase of entropy with the temperature could be the consequence of a more disordered bulk water structure at higher temperatures due to the perturbation by thermal movements. In the process of complexation, the solvating water molecules are released to an already expanded and more disordered bulk solvent [27]. As a result, the net gain in the complexation entropy is larger at higher temperatures.…”
Section: Enthalpy Of Complexation Between U(vi) and Sulfate At Elevatmentioning
confidence: 99%
“…At each temperature, the spectra of UO 2þ 2 were slightly red-shifted as the concentration of nitrate was increased. Analysis by the Hyperquad program indicated that there are two absorbing species of U(VI) and the spectra were best-fitted with the formation of a 1:1 complex, UO 2 …”
Section: Calorimetrymentioning
confidence: 99%
“…The SIT (specific ion interaction) approach originated from the Brønsted-Guggenheim-Scatchard model [33 -35] has been used to calculate the equilibrium constants at zero ionic strength. For reaction (2), the equilibrium constant at the standard state (lg K m in molality) are calculated by:…”
Section: Calculation Of Stability Constants At Variable Temperatures mentioning
confidence: 99%
See 1 more Smart Citation
“…Tda is a versatile ligand that has been widely explored employing its multidendate and chelating coordination abilities with many metals. It forms complexes with different metal ions, such as lanthanides (Zhang et al, 2002), cobalt (Grairrane, Pastor, Alvrez, Mealli et al, 2005), magnesium , zinc (Grairrane et al, 2006;Wyrzykowski et al, 2013), copper (Alarcon-Payer et al, 2005;Baggio et al, 1999), vanadium (Alvarez et al, 2010), lead (Gabriel et al, 2013;Wu et al, 2013), tin (Sandhu & Sharma, 1996), calcium and strontium (Grairrane et al, 2007), uranium(VI) (Kirishima & Sato, 2014;Di Bernardo et al, 2006), ruthenium (Zangl et al, 2009) and manganese (Grairrane et al, 2003(Grairrane et al, , 2011. Multidentate macrocyclic ligands have been synthesized using Tda and triazine (Aghatabay et al, 2009;Steenland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%